The lean product design and development journey : a practical view - Pessôa, Marcus Vinicius Pereira; Trabasso, L. G. (Springer, 2016)
This book presents a series of high performance product design (PD) and development best practices that can create or improve product development organization. In contrast to other books that focus only on Toyota or other individual companies applying lean IPD, this book explains the lean philosophy more broadly and includes discussions of systems engineering, design for X (DFX), agile development, integrated product development, and project management. The "Lean Journey" proposed here takes a value-centric approach, where the lean principles are applied to PD to allow the tools and methods selected to emerge from observation of the individual characteristics of each enterprise. This means that understanding lean product development (LPD) is not about knowing which tools are available but knowing how to apply the philosophy. The book comes with an accompanying manual with problems and solutions available on Springer Extras.